Students’ Scientific Argumentation in Ethno-Thermochemistry: A Toulmin-Based Analysis Across Argumentation Levels - Nur Widia Ky. Martam; Lukman Abdul Rauf Laliyo; Thayban Thayban; Astin Lukum; Julhim S. Tangio (Jambura Journal of Educational Chemistry, 2026)
Low students’ scientific argumentation skills remain a concern in chemistry learning because students are required not only to understand concepts but also to explain phenomena logically, based on evidence, and in accordance with scientific principles. In thermochemistry learning, ethno-thermochemistry contexts can help students connect abstract energy transformation concepts with cultural phenomena closely related to their daily lives. However, studies investigating students’ scientific argumentation skills within ethno-thermochemistry contexts, particularly based on the components of the Toulmin Argument Pattern (TAP), are still limited. Therefore, this study aims to analyze students’ scientific argumentation skills in ethno-thermochemistry learning using TAP. This study employed a descriptive quantitative design involving 101 high school students. Data were collected through a multiple-choice test consisting of 36 items representing six ethno-thermochemistry phenomena. The instrument measured six argumentation components, namely claim, grounds, warrant, backing, qualifier, and rebuttal. The results revealed a consistent pattern in students’ argumentation, with high achievement in lower-level components (claim: 65–77%) and moderate achievement in grounds and warrant, followed by a significant decline in higher-level components, particularly backing, qualifier, and rebuttal (25–40%). These findings indicate that students are able to construct initial ideas and basic justifications but still experience difficulties in evaluative reasoning. Furthermore, ethno-thermochemistry contexts appear to support contextual understanding and activate students’ prior knowledge, but they have not been optimal in promoting higher-order argumentation skills. This study emphasizes the importance of explicit argumentation scaffolding in ethno-thermochemistry-based chemistry learning to support students’ scientific reasoning.